BOOK REVIEW OF INGGS, JUDITH AND WEHRMEYER, ELLA. AFRICAN PERSPECTIVES ON LITERARY TRANSLATION. ROUTLEDGE, 2021. - Silva Fernandes, Joyce (Entheoria: Cadernos de Letras e Humanas, 2023)
Book Review of Inggs, Judith and Wehrmeyer, Ella. African Perspectives on Literary Translation. Routledge, 2021.